Digital Learning for Future Science Learning: A Systematic Literature Review - Zainal Abidin; Arie Wahyu Prananta; Asmiddin (Postgraduate, University of Mataram, 2023)
In the 21st Century, technology is increasingly fast, even getting information is considered very easy with the existence of digital media which becomes a facilitator to be able to communicate with each other share and exchange information. Of course, with the development of time, feel left behind if you don't keep up with technological developments. Education in the digital era is mandatory education integrating Information and Communication Technology into all areas of lessons. Students need to have the ability to think to be able to answer the problems they face and education must be able to facilitate developing this thinking ability. The research aims to examine Digital Learning for Future Science Learning. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines We must know and practice changes in education and learning patterns at all levels of education by describing the characteristics of learning that are currently needed. The results of this research explain that learning and learning have theory and implementation to be applied at every level of education, several learning media are carried out, and currently, digital learning media is increasingly widespread and developing with the times.